Quality Of Work-Life Of Employees In The Agricultural Sector With Reference To Ambasamudram Taluk (International Journal of Food and Nutritional Sciences, 2022)
The Quality of Work Life is very significant in the context of a commitment to work, motivation and job performance. It is also meant to facilitate the gratification of human needs and goal achievement. Work-life naturally means the life of workers, physical and intellectual, in their work environment in office or factory or field-working. Quality of work life is a Person’s life. It covers a person’s feelings about every dimension of work, including economic rewards and benefits, security, working condition, Organizational and interpersonal relations and their intrinsic meaning in a person’s life. Therefore, we can say Q.W.L. is concerned with improving life at and outside work. The present study is to analyse the Quality of work-life of employees in the Agricultural sector with reference to Ambasamudram Taluk.